Using Buck's Fascia as an Integral Covering in Urethroplasty to Restore the Anatomical Structure of the Penis in One-Stage Hypospadias Repair: A Multicenter Chinese Study Comprising 1,386 Surgeries - Zhang, Yin; Chao, Min; Zhang, Wei-ping; Tang, Yun-man; Chen, Hai-chen; Zhang, Kai-ping; Lu, Ru-gang; Zhang, Xian-sheng; Lou, Dong-hua (Frontiers in Pediatrics, 2021)
Objectives: To investigate the feasibility and efficacy of urethroplasty with a Buck’s fascia integral-covering technique (BFIC) to wrap and restore the normal anatomical structure of the penis in one-stage hypospadias surgery. Methods: One-stage surgeries for hypospadias management were performed using BFIC from January 2016 to September 2020 at four high-volume medical centers in China. The technique integrates Buck’s fascia with glans wings to mobilize and wrap the urethra and restore penile anatomical relationships. The clinical data, postoperative follow-up data, and complications were recorded and the results analyzed. Results: A total of 1386 patients were included in the study: 1260 cases of primary hypospadias and 126 cases of re-operations. Distal in 382 cases (27.6%), mid-shaft in 639 (46.1%), proximal in 365 (26.3%). Tubularized incised plate (TIP) in 748 cases, Inlay-graft in 124, Onlay-graft in 49, Mathieu in 28, Free-tube graft urethroplasty in 406, and 31 of hybrid procedures. 1142 patients (82.4%) were found to have penile curvature (>10°) after artificial erection and all corrected by dorsal plication/s or transection of the urethra plate (UP) simultaneously. The median followed up time was 27 months (6 to 62). A total of 143 (10.3%) complications were recorded: 114 (9.0%) in the primary operations and 29 (23%) in the re-operations, 15 (3.9%) in distal hypospadias, 61 (9.5%) in mid-shaft and 67 (18.4%) in proximal. The complication rate in UP preservation and transection was 10.1% and 10.8% respectively. Of all case complications, there were 73 (5.2%) of fistula, 10 (0.6%) of dehiscence, 22 (1.6%) of meatal stenosis, 21 (1.5%) of stricture, 6 (0.7%) of diverticulum, resident curvature in 11 cases (1.2%). The overall complication rate in TIP and Free-tube procedure was 9.8% and 9.9% respectively, and fistula occurred in primary TIP of 33 cases (4.9%). Conclusions: Buck’s fascia with the glans can be used as an integral covering technique in one-stage distal to proximal hypospadias and primary or re-operative hypospadias repair. It is safe, feasible, and effective for the repair of hypospadias.